2013
DOI: 10.1007/10_2013_185
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Systems: Functional Modules for Synthetic and Chemical Biology

Abstract: : The main goal of cell-free protein synthesis is to produce correctly folded and functional proteins in reasonable amounts for further downstream applications. Especially for eukaryotic proteins, functionality is often directly linked to the presence of posttranslational modifications. Thus, it is of highest interest to develop novel cell-free expression systems that enable the synthesis of posttranslationally modified proteins. Here we present recent advances for the synthesis of glycoproteins, proteins cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 100 publications
(146 reference statements)
1
29
0
Order By: Relevance
“…The determination of the optimal concentration of the previously described E. coli-derived mutant synthetase eAzFRS (Chin et al, 2003;Takimoto et al, 2009) in combination with a natural amber suppressor tRNA CUA from E. coli (Edwards and Schimmel, 1990) used in this study, was performed stochastically in batch-formatted reactions (data not shown). Based on earlier findings which indicated a significant influence of the cation concentration on the yield of cell-free synthesized proteins with incorporated AzF (Stech et al, 2013), we applied the automated workflow to an amber suppression screening varying the Mg 2+ concentration. Moreover, we also implemented a second dimension screening procedure using an iterative development process at different insect cell lysate concentrations.…”
Section: Application Of the Automated Synthesis For Amber Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of the optimal concentration of the previously described E. coli-derived mutant synthetase eAzFRS (Chin et al, 2003;Takimoto et al, 2009) in combination with a natural amber suppressor tRNA CUA from E. coli (Edwards and Schimmel, 1990) used in this study, was performed stochastically in batch-formatted reactions (data not shown). Based on earlier findings which indicated a significant influence of the cation concentration on the yield of cell-free synthesized proteins with incorporated AzF (Stech et al, 2013), we applied the automated workflow to an amber suppression screening varying the Mg 2+ concentration. Moreover, we also implemented a second dimension screening procedure using an iterative development process at different insect cell lysate concentrations.…”
Section: Application Of the Automated Synthesis For Amber Suppressionmentioning
confidence: 99%
“…On the one hand, fluorescent amino acid derivatives such as BODIPY-TMR-lysine can be directly incorporated into proteins in a statistical manner by sense codon reassignment using pre-charged tRNAs which allows for a sensitive detection of synthesized proteins . On the other hand, the site-directed incorporation of p-Azido-l-phenylalanine (AzF) based on amber suppression, mediated by an orthogonal tRNA/synthetase pair derived from E. coli, enabled us to fluorescently modify cell-free synthesized human erythropoietin in a selective manner by Staudinger ligation (Stech et al, 2013;Quast et al, 2014). The employment of amino acids with selective reactivity facilitates a subsequent modification of proteins to introduce a variety of different characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, protein synthesis is disconnected from cell fate and the protein synthesis reaction itself is not constrained by a cell wall, meaning that reaction conditions are accessible from the outside of the reaction vessel [5,7,42].…”
Section: Cell-free Protein Synthesismentioning
confidence: 99%
“…These features are made possible as the cell extract contains translationally active, endogenous microsomal vesicles having their origin in the ER of the insect cells. These vesicles are formed during the lysate preparation procedure, where the native structure of the ER is ripped, followed by its rearrangement and formation of smaller compartments designated as microsomal vesicles [5]. Due to the presence of these vesicles, target proteins can be translocated into the lumen of these vesicles, if they are fused to an appropriate signal sequence [65].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation